Within-community variation of interspecific divergence patterns in passerine gut microbiota - Kubovčiak, Jan; Schmiedová, Lucie; Albrecht, Tomáš; Těšický, Martin; Tomášek, Oldřich; Kauzálová, Tereza; Kreisinger, Jakub (Ecology and evolution, 2022)
Gut microbiota (GM) often exhibit variation between different host species and co-divergence with hosts' phylogeny. Identifying these patterns is a key for understanding the mechanisms that shaped symbiosis between GM and its hosts. Therefore, both GM-host species specificity and GM-host co-divergence have been investigated by numerous studies. However, most of them neglected a possibility that different groups of bacteria within GM can vary in the tightness of their association with the host. Consequently, unlike most of these studies, we aimed to directly address how the strength of GM-host species specificity and GM-host co-divergence vary across different GM clades. We decomposed GM communities of 52 passerine species (394 individuals), characterized by 16S rRNA amplicon sequence variant (ASV) profiles, into monophyletic Binned Taxonomic units (BTUs). Subsequently, we analyzed strength of host species specificity and correlation with host phylogeny separately for resulting BTUs. We found that most BTUs exhibited significant host-species specificity in their composition. Notably, BTUs exhibiting high host-species specificity comprised bacterial taxa known to impact host's physiology and immune system. However, BTUs rarely displayed significant co-divergence with host phylogeny, suggesting that passerine GM evolution is not shaped primarily through a shared evolutionary history between the host and its gut microbes.
Keywords: co‐divergence; metabarcoding; 16S rRNA; gut microbiota; passerines